2016
DOI: 10.1016/j.chom.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Altered Virome and Bacterial Microbiome in Human Immunodeficiency Virus-Associated Acquired Immunodeficiency Syndrome

Abstract: SUMMARY Human immunodeficiency virus (HIV) infection is associated with increased intestinal translocation of microbial products and enteropathy as well as alterations in gut bacterial communities. However, whether the enteric virome contributes to this infection and resulting immunodeficiency remains unknown. We characterized the enteric virome and bacterial microbiome in a cohort of Ugandan patients, including HIV-uninfected or HIV-infected subjects and those either treated with anti-retroviral therapy (ART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
342
13
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(396 citation statements)
references
References 53 publications
23
342
13
3
Order By: Relevance
“…Of note, correlations between CD4 counts and gut microbial profiles have yielded conflicting results in HIV-infected individuals. Consistent with the above findings in the URT, certain studies have reported a lack of association between CD4 counts and gut microbial composition [55, 56], whereas others have reported associations between CD4 counts and enrichment of certain bacterial taxa [57, 58]. Thus in addition to CD4 counts, other markers of HIV progression should be included in analyses for more robust results.…”
Section: The Bacterial Microbiomesupporting
confidence: 53%
“…Of note, correlations between CD4 counts and gut microbial profiles have yielded conflicting results in HIV-infected individuals. Consistent with the above findings in the URT, certain studies have reported a lack of association between CD4 counts and gut microbial composition [55, 56], whereas others have reported associations between CD4 counts and enrichment of certain bacterial taxa [57, 58]. Thus in addition to CD4 counts, other markers of HIV progression should be included in analyses for more robust results.…”
Section: The Bacterial Microbiomesupporting
confidence: 53%
“…Changes in various components of the microbiome have been observed in association with multiple human diseases (1)(2)(3)(4). Prominent among diseases that are influenced by microorganisms is type 1 diabetes (T1D), a disease involving an autoimmune attack on the insulin-secreting beta cells of the pancreatic islets of Langerhans.…”
mentioning
confidence: 99%
“…Changes in intestinal viruses have been observed in patients with inflammatory bowel disease and AIDS (2)(3)(4)12), indicating that changes in the virome can be associated with infectious and inflammatory diseases. In some cases, these changes involve eukaryotic viruses, whereas in other cases, disease-associated changes in bacteriophages have been identified.…”
mentioning
confidence: 99%
“…Using a panenterovirus real-time PCR, we also showed significantly lower C T values in the acute-and chronic-diarrhea groups of animals, supporting generally higher picornavirus RNA loads in diarrheic cases than in the healthy group. The notion that the percentage of sequence read numbers generally reflects the viral load is also supported by studies reporting a correlation between the viral reads and real-time PCR-estimated viral loads (40)(41)(42). A related virome study of SIV-infected rhesus macaques also showed a greater percentage of picornavirus reads (all genotypes combined) in the feces of animals with SIV enteropathy than in a non-SIV-infected control group (15).…”
Section: Discussionmentioning
confidence: 86%